Development of Algorithms for Adaptation of Mathematical Models of the Atmospheric Block of the Technological Complex of Primary Oil Refining - Safarova, A.A. (Herald of Azerbaijan Engineering Academy, 2025)
The conducted analyses have shown that one of the main guarantors of economic efficiency of new technological facilities implemented in the oil refining industry on the basis of these projects is, as a rule, modern automation and control systems used in them. However, it should be noted that the enterprises of the oil refining industry have reserves for increasing their economic efficiency, depending on the modern level of automation and control systems of technological facilities. Therefore, taking into account all the above, the presented paper deals with the solution of the problem of adaptation of mathematical models of the optimal control system of the atmospheric unit at the level of operational control in the technological complex of primary oil refining.